НИЙГЭМ ЭДИЙН ЗАСГИЙН ХӨГЖИЛД УЛС ТӨРИЙН ХҮЧИН ЗҮЙЛИЙН НӨЛӨӨЛӨЛ - Д.Болд-Эрдэнэ (Politology, 2023)
Abstract: Political factor has a crucial role in social and economic development. Fundamental research of political factor impact is essential in order to get a correct vision of trends in political and economic development. Thus, some important issues related to political and socioeconomic development will be discussed in the article.